2021
DOI: 10.1002/hep.31658
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid‐Cell–Specific IL‐6 Signaling Promotes MicroRNA‐223‐Enriched Exosome Production to Attenuate NAFLD‐Associated Fibrosis

Abstract: BaCKgRoUND aNDS aIMS: NAFLD is associated with elevation of many cytokines, particularly IL-6; however, the role of IL-6 in NAFLD remains obscure. The aim of this study was to examine how myeloid-specific IL-6 signaling affects NAFLD by the regulation of antifibrotic microRNA-223 (miR-223) in myeloid cells.appRoaCH aND ReSUltS: Patients with NAFLD or NASH and healthy controls were recruited, and serum IL-6 and soluble IL-6 receptor α (sIL-6Rα) were measured. Compared to controls, serum IL-6 and sIL-6Rα levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
123
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(127 citation statements)
references
References 47 publications
(119 reference statements)
4
123
0
Order By: Relevance
“…Mice were injected with CCl 4 for 4 weeks followed by Gfp-or miR-223 expressing adenovirus injection for 2 weeks. As we previously reported, overexpression of miR-223 led to decreased fibrogenic gene expression and attenuated CCl 4 -induced liver fibrosis [23]. In the current study, we demonstrated that TAZ and IHH protein levels in hepatocytes were markedly decreased in mice injected with miR-223-expressing adenovirus (Ad-miR-223) (Fig.…”
Section: Gli2 Is a Target Of Mir-223 In Hscssupporting
confidence: 78%
See 1 more Smart Citation
“…Mice were injected with CCl 4 for 4 weeks followed by Gfp-or miR-223 expressing adenovirus injection for 2 weeks. As we previously reported, overexpression of miR-223 led to decreased fibrogenic gene expression and attenuated CCl 4 -induced liver fibrosis [23]. In the current study, we demonstrated that TAZ and IHH protein levels in hepatocytes were markedly decreased in mice injected with miR-223-expressing adenovirus (Ad-miR-223) (Fig.…”
Section: Gli2 Is a Target Of Mir-223 In Hscssupporting
confidence: 78%
“…Restoration of hepatic miR-223 ameliorates steatosis and fibrosis in HFD-fed Ldlr KO mice 15 . In addition, the therapeutic effect of adenovirus-mediated overexpression of miR-223 was also recently demonstrated in liver fibrosis induced by chronic CCl 4 treatment 23 . In the current study, we demonstrated that overexpression of miR-223 in hepatocytes can also ameliorate CCl 4- induced liver fibrosis by secreting TAZ-targeting IHH and by releasing miR-223-enriched EVs.…”
Section: Discussionmentioning
confidence: 90%
“…For example, IL-6 reportedly stimulates myeloid cells to release exosomes containing miR-223 that are absorbed by hepatocytes. Subsequently, miR-223 alleviates liver fibrosis by suppressing the expression of its profibrotic target genes, including Nlrp3, Igf1r, Cxcl10, and TAZ [88]. Additionally, hepatocytes can absorb neutrophil-derived miR-223-enriched EVs in a LDLR-and apolipoprotein E (APOE)-dependent manner [99].…”
Section: The Role Of Mirnas In Nafld Related Hepatic Inflammationmentioning
confidence: 99%
“…It is increasingly recognized that EVs are involved in the occurrence and development of hepatic inflammation in NASH. The function of miR-223-enriched EVs in inflammation has been excellently illustrated by Wang et al [88] and He et al [99].…”
Section: The Role Of Mirnas In Nafld Related Hepatic Inflammationmentioning
confidence: 99%
See 1 more Smart Citation